Organizational Reform in the Hungarian Hospital Sector : Institutional Analysis of Hungarian Hospitals and the Possibilities of Corporatization - Réthelyi, János M.; Miskovits, Eszter; Szócska, Miklós K. (World Bank, Washington, DC, 2013)
The organizational reform of public hospitals is part of the health policy agenda worldwide as a reaction to inefficient and low quality performance in public institutions. A central theme of these reforms is the possibility of improving performance in public settings under semiautonomous circumstances. Central and East European countries face the problem of an oversized and hospital-based health care system inherited historically from the former centralized totalitarian political system. The authors analyze the Hungarian Hospital sector in terms of recent changes and the effect of these on organizational modalities shown earlier to play a crucial role in the performance of public hospitals. Organizational theory and the "organizational modality - incentive regime" model is used to describe incongruence and general incoherence in the everyday functioning of Hungarian hospitals. Finally the possibilities and long-term effects of corporatization and marketing changes are examined according to recent political and legislative changes and a corresponding case study.